Tyrosine 625 plays a key role and cooperates with tyrosine 630 in MPL W515L-induced signaling and myeloproliferative neoplasms. Issue 1 (December 2016) - Yu, Chunjie; Yang, Qiong; Chen, Yuhong; Wang, Demin; Levine, Ross; Crispino, John; Wen, Qiang; Huang, Zan
Abstract Background Myeloproliferative neoplasms (MPN) are a group of blood cancers that boost normal blood cell production in the bone marrow. Abnormal mutations in stem cells were found accompanying with the occurrence of MPN. It has been shown that MPL mutations (MPL W515L or MPL W515K) were involved in patients with MPN. Since tyrosine residues 625 and 630 mediate normal MPL signaling, whether them affect MPL W515L-induced myeloproliferative neoplasms (MPNs) is unknown. Results In this study, we further tested their functions in MPL W515L-induced myeloproliferative neoplasms (MPNs) by substituting either or both of them with phenylalanine in MPL W515L (termed as MPL515/625, MPL515/630 and MPL515/625/630, respectively). In vitro, MPL515/630 but not MPL515/625 or MPL515/625/630 retained the ability to induce TPO-independent proliferation and increase colony-forming unit megakaryocytes (CFU-Mk). Accordingly, differential activation of the downstream signaling by four mutants was observed and constitutively active STAT5 or AKT instead of STAT3 partially compensated MPL515/625/630 function. Further support this, STAT5-deficiency impaired MPL W515L-induced CFU-Mk expansion. In vivo, MPL515/630 but not MPL515/625 or MPL515/625/630 induced typical features of MPNs with high WBC and platelet counts, splenomegaly, hepatomegaly and hypercellularity in the bone marrow. Surprisingly, MPL515/625 also caused hypercellularity of bone marrow and splenomegaly without any other significant features. We also observed differential effects of the four mutants on progenitors, myeloid cells and megakaryocytes. Conclusions Our studies have revealed distinct features of tyrosine sites 625 and 630 in mediating MPL W515L-induced megakaryocyte hyperproliferation and MPNs. Our study also suggests that MPL cytosolic phosphorylated Y625 and flanking amino acids could become targets for pharmacologic inhibition in MPNs.